Molecular phylogenetic and morphological analyses of Oidium heveae, a powdery mildew of rubber tree - Limkaisang, Saranya; Kom-Un, Sawanee; Furtado, Edson Luiz [UNESP]; Liew, Kon Wui; Salleh, Baharuddin; Sato, Yukio; Takamatsu, Susumu (The Mycological Society of Japan, 2005)
Powdery mildew of rubber tree caused by Oidium heveae is an important disease of rubber plantations worldwide. Identification and classification of this fungus is still uncertain because there is no authoritative report of its morphology and no record of its teleomorphic stage. In this study, we compared five specimens of the rubber powdery mildew fungus collected in Malaysia, Thailand, and Brazil based on morphological and molecular characteristics. Morphological results showed that the fungus on rubber tree belongs to Oidium subgen. Pseudoidium. Nucleotide sequence analysis of the ribosomal DNA internal transcribed spacer (ITS) region and the large subunit rRNA gene (28S rDNA) were conducted to determine the relationships of the rubber powdery mildew fungus and to link this anamorphic fungus with its allied teleomorph. The results showed that the rDNA sequences of the two specimens from Malaysia were identical to a specimen from Thailand, whereas they differed by three bases from the two Brazilian isolates: one nucleotide position in the ITS2 and two positions in the 28S sequences. The ITS sequences of the two Brazilian isolates were identical to sequences of Erysiphe sp. on Quercus phillyraeoides collected in Japan, although the 28S sequences differed at one base from sequences of this fungus. Phylogenetic trees of both rDNA regions constructed by the distance and parsimony methods showed that the rubber powdery mildew fungus grouped with Erysiphe sp. on Q. phillyraeoides with 100% bootstrap support. Comparisons of the anamorph of two isolates of Erysiphe sp. from Q. phillyraeoides with the rubber mildew did not reveal any obvious differences between the two powdery mildew taxa, which suggests that O. heveae may be an anamorph of Erysiphe sp. on Q. phillyraeoides. Cross-inoculation tests are required to substantiate this conclusion.
Keywords: 28S rDNA; Erysiphe; Hevea brasiliensis; ITS; Quercus phillyraeoides